The Prose Poem of Salim Agha Qazlbash: A Critical View (DARYAFT, 2022)
Dr. Salim Agha is a renowed name in the Urdu .He is one of the most respectable name, who nurtured the genre of  “Prose poem” .He plunged into most of the literary genres and tested his potential there. It is beyond any doubt whatever his imaginative skills created that is superlative in class and construction. In the field of “Urdu Prose poem” he gained a respectable status due to his best style of writings. He portrays the colors of life and universe in his prose poems. It shows his love for nature and for life.  Through this article an efforts has been made to express the critical view about his Prose poem writing.
Keywords: Bodliar; Salim Agha Qazalbash; Dr Wazir Agha; Prose Poem; Critical View; Imaginative skills